2013
DOI: 10.1098/rspb.2012.2397
|View full text |Cite
|
Sign up to set email alerts
|

Phenological response of sea turtles to environmental variation across a species' northern range

Abstract: Variations in environmental parameters (e.g. temperature) that form part of global climate change have been associated with shifts in the timing of seasonal events for a broad range of organisms. Most studies evaluating such phenological shifts of individual taxa have focused on a limited number of locations, making it difficult to assess how such shifts vary regionally across a species range. Here, by using 1445 records of the date of first nesting for loggerhead sea turtles (Caretta caretta) at different bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 55 publications
2
56
0
1
Order By: Relevance
“…timing of prebreeding migrations) might be flexible and controlled by the environment (e.g. by sea temperatures; Mazaris et al 2013). …”
Section: Adult Loggerhead Turtlesmentioning
confidence: 99%
“…timing of prebreeding migrations) might be flexible and controlled by the environment (e.g. by sea temperatures; Mazaris et al 2013). …”
Section: Adult Loggerhead Turtlesmentioning
confidence: 99%
“…Such shifts in nesting phenology are relatively slow compared to other sea turtle species at higher-latitude nesting beaches (e.g. Weishampel et al 2004, Pike et al 2006, Mazaris et al 2013. Moreover, the shift observed at Playa Grande is the first time a shift for nesting later in the year has been reported for any sea turtle population.…”
Section: Discussionmentioning
confidence: 82%
“…The factors governing nesting phenology have only been investigated for only 2 sea turtle species: loggerhead turtles Caretta caretta (Weishampel et al 2004, Pike et al 2006, Mazaris et al 2013) and green turtles Chelonia mydas (Pike 2009, Weishampel et al 2010, Dalleau et al 2012. For both species, it has been repeatedly shown that the timing of the nesting season is influenced by the sea surface temperature of the waters near the nesting grounds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…También se ha mostrado que el clima en algunas ocasiones tiene influencia a esta escala, tanto en la ocurrencia de la temporada de reproducción como en el inicio, duración y fin a la anidación de las tortugas (Mazaris et al 2013, Neeman et al 2015, Álvarez-Acosta 2016.…”
Section: Escala Espacial Mediaunclassified